Prevention of natural grassland invasion by Eragrostis plana Nees using ecological management practices - Focht, Telmo (2012)
The objective of this research was to evaluate the effects of different types of disturbance on the ability of the natural grassland to avoid the invasion of Eragrostis plana Nees (South African lovegrass). The experiment was carried out in Dom Pedrito, Rio Grande do Sul, Brazil, in an area free of South African lovegrass, from Feb. 2004 to Apr. 2007. The treatments were: 1) grassland management regimes: exclusion; low grazing intensity (rotational grazing), ±10 cm; and high grazing intensity (continuous grazing), ±5 cm; 2) initial levels of soil disturbance: high grassland, ±10 cm; low grassland, ±5 cm height; and low grassland with scarified soil; 3) fertilization regimes: without fertilization; phosphorus; and nitrogen. The experimental design was a split-split-plot type in complete blocks, with three replicates. Three winter cultivated species - Trefoil repens L., Lotus corniculatus L., Lolium multiflorum Lam. and South African lovegrass - were sown in 54 split-splitplots (split-plots: low grassland, and low grassland with scarified soil). The other 27 split-split-plots (split-plots: high grassland) were sown only with South African lovegrass. The grassland height, plant number of South African lovegrass, grassland dry mass and photosynthetic active radiation intercepted (FARint) at the soil level were recorded. The fertilization regimes did not influence the South African lovegrass plant number. The initial levels of soil disturbance and grassland management regimes influenced the invasion of South African lovegrass. The invasion was favored by the lower grassland height and lower forage mass, higher intensity of the soil disturbance, and higher FARint due to the continuous grazing. On the contrary, higher grassland height, higher forage mass, lower soil disturbance and lower FARint, associated with rotational grazing or exclusion, showed higher potential to control the invasion of South African lovegrass in the natural grassland.